PENGARUH PEMBUATAN KLIPING MEDIA MASSA TERHADAP PRESTASI BELAJAR IPS - Muhammad Nur; Anisaurrohmah Anisaurrohmah (Cross-border, 2021)
This research was to test alternative of learning by mass media clippings in order to increase the creativity and learning achievement of students at MTsN 2 Tanah Laut. A quantitative approach with a quasi-experimental design for the experimental class who received learning by making mass media clippings and the control class who did not make clippings. Data were analyzed using t-test of SPSS version 23. The results proved that the learning achievement of social studies in the experimental class which made mass media clippings as a source of social studies learning was higher than the control class who did not make mass media clippings. The results of interviews and field observations also show that the attitudes and interests of students and even teachers are more positive so that it has a positive impact on improving student learning achievement.